2002
DOI: 10.3171/jns.2002.97.4.0803
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic pain by using intrathecal drug therapy compared with conventional pain therapies: a cost-effectiveness analysis

Abstract: In patients who respond to this treatment, IDT is cost effective in the long term despite high initial costs of implantable devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 19 publications
(23 reference statements)
0
95
1
5
Order By: Relevance
“…Only limited data are available on the long-term dose increase in patients with intrathecal therapy for pain and spasticity. One study observing 16 pain patients reported a ninefold increase in the daily morphine dosage after 2 years, 17 while in a larger study of 120 patients an increase of only 74% after 3.4 years was reported. 18 However, in 40 patients treated for spasticity, a 2.6-fold increase of the daily baclofen dosage was found.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited data are available on the long-term dose increase in patients with intrathecal therapy for pain and spasticity. One study observing 16 pain patients reported a ninefold increase in the daily morphine dosage after 2 years, 17 while in a larger study of 120 patients an increase of only 74% after 3.4 years was reported. 18 However, in 40 patients treated for spasticity, a 2.6-fold increase of the daily baclofen dosage was found.…”
Section: Discussionmentioning
confidence: 99%
“…Tab. 1) liegen in: F der effektiven Schmerzlinderung [1,27,30,34], F der relativ selektiven Analgesie mit geringer Beeinträchtigung taktiler, motorischer oder sympathischer Funktionen sowie der Reduktion der Nebenwirkungen auf ein Minimum [21], F der signifikanten Reduktion der oralen Medikation, wobei sie bei Tumorpatienten deutlicher gesenkt werden kann als bei chronisch nichtmalignen Patienten, F der besseren Beweglichkeit und Funktionalität [38], F der besseren Lebensqualität [ …”
Section: Stellenwertunclassified
“…Sie sind kein absoluter Ausschlussgrund vom Verfahren, können aber ggf. im Einzelfall zum Ausschluss führen [20,21].…”
Section: Psychologische/ Psychiatrische Aspekteunclassified
“…5,6 In patients with refractory neuropathic pain, administration of combination therapy of two or more agents with synergistic mechanisms, 7 or implantation of neuromodulation devices, such as spinal cord stimulators or intrathecal drug delivery pumps, can be required. 8,9 Although neuropathic pain may result from insults to both the central and peripheral nervous systems, most clinical studies have focused primarily on a small number of specific peripheral neuropathic pain syndromes. While pharmacological studies have been conducted in DPN, PHN and to some degree in trigeminal neuralgia (TN), spinal cord stimulation trials have been carried out in the neuropathic component of failed back surgery syndrome (FBSS) and in complex regional pain syndrome (CRPS).…”
Section: A N a G E M E N T O F N E U R O P A T H I C P A I Nmentioning
confidence: 99%
“…Nonetheless, several cohort studies suggest that the use of opioids alone or in combination with local anaesthetics, alpha adrenergic blockers, or the new selective Ntype calcium channel blocker ziconotide can be helpful in otherwise refractory patients. 9 Furthermore, surgical procedures such as mirconeurosurgery, resection of neuromas and surgical implantation of neurostimulators can be indicated in selective patients. 21 Lastly, as mentioned earlier, neuropathic pain is often associated with significantly impaired functioning and reduced quality of life.…”
Section: N E U R O M O D U L a T I O N T E C H N I Q U E Smentioning
confidence: 99%